A CULTURE OF KINSHIP: CHINESE GENEALOGIES AS A SOURCE FOR RESEARCH IN DEMOGRAPHIC ECONOMICS–CORRIGENDUM. (20th December 2016) - Shiue, Carol H.
Abstract : On page 476 of the text, in the second paragraph it states: "In comparison, the percent of individuals whocan be linked in the Chinese Eight Banner Registers is 14.54% or 24.76% for one generation, depending on whether one considers Liaoning or Heilongjiang Province [Dong et al. (2015)]." This should instead read: "In comparison, the percent of individuals whocan't be linked in the Chinese Eight Banner Registers is 14.54% or 24.76% for one generation, depending on whether one considers Liaoning or Heilongjiang Province [Dong et al. (2015)]." The authors apologise for this error.